IT Skills Required by Library Professionals Working in the University Libraries of Lahore - Khurram Shahzad , Muhammad Tariq (IJoLIS, 2024)
Purpose: The major objective of the study was to explore the status of IT skills required by library professionals working in university libraries of lahore.